Development of a Renewable Energy Model Based on Discovery Learning to Improve Students’ Critical Thinking Skills - Syifa Fauzia; Erina Hertanti; Fuji Hernawati Kusumah (Jurnal Penelitian Pembelajaran Fisika, 2026)
The low critical thinking skills of students in renewable energy learning and the limited availability of teaching aids that integrate various renewable energy sources are the background of this research. This research aims to develop a renewable energy model based on discovery learning to improve students' critical thinking skills. This research uses a development research model consisting of four stages: preliminary research, prototyping stage, formative evaluation and summative evaluation. This research was conducted at MA Al-Khairiyah North Jakarta involving experts, teachers, and grade 10 students. The model integrates two renewable energy sources (solar and wind) in one system equipped with student worksheets based on discovery learning. Data were collected through expert validation questionnaires, student and teacher response questionnaires, and critical thinking ability tests. The results showed that the model met the criteria of feasibility, practicality, and effectiveness. Based on validation by media experts and subject matter experts, the model obtained percentage scores of 83.24% and 86%, respectively, with an average of 84.62%, included in the very feasible category. The practicality assessment showed a score of 93.75% from students and 87.5% from teachers, both categorized as very practical. The effectiveness aspect received a score of 90.6% from teachers, categorized as very effective. Students' critical thinking skills showed consistent improvement across all stages of the evaluation with n-gain values ​​ranging from 0.30 to 0.46, included in the moderate category. In conclusion, the renewable energy model based on discovery learning has proven effective in helping students understand the concept of renewable energy and improve their critical thinking skills through active learning experiences and observations.